MANFAAT PEMANTAUAN DALAM BIDANG PENGELOLAAN LINGKUNGAN - Satmoko Yudo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
In the next World Free Trade Era, presumably 70% industrial growth, especially in Java will be centered around the cities and this situation will increase environmental pollutions. The government continuously do the efforts to keep down the problems although there are also many pollution cases that couldn’t be completed. Because of lack in continous control and monitor by institution which handle environmental problems.This paper explains the role of monitoring environmental management, especially in monitoring environmental pollutions. As supporting data this paper discuss a case about using information technology in environmental managemnet in Japanesse Environmental Offices. This case shows that monitoring environmental pollutions, air water and others is an important job which is done by environmental departement in Japanese local government office. The environmental pollution monitoring has an important role in controling environmental pollutions.